Early fixation strategies for high energy pelvic ring injuries – the Zurich algorithm. Issue 10 (October 2021) - Tiziani, Simon; Halvachizadeh, Sascha; Knöpfel, Adrian; Pfeifer, Roman; Sprengel, Kai; Tarkin, Ivan; Pape, Hans-Christoph
Highlight: Level of evidence. Abstract: In isolated high energy pelvic ring injuries, early surgical and nonsurgical fixation belongs to the rescue tools required for rapid recovery. With the increasing use of pelvic binders on scene, these patients frequently arrive in a better condition at the level I trauma centre than without any measures of immobilisation. We describe our surgical tools to achieve rapid fixation within the first hours after arrival, taking into account if additional injuries or special stations are relevant